Effects of NPB anode buffer layer on charge collection in ZnO/MEH-PPV hybrid solar cells - 龚伟 徐征 赵谡玲 刘晓东 樊星 杨倩倩 孔超 (Chinese physics B, 2013)
We investigate the effects of （N,N’-diphenyl）-N,N’-bis（1-naphthyl）-1,1’-biphenyl-4,4’-diamine （NPB） buffer layers on charge collection in inverted ZnO/MEH-PPV hybrid devices. The insertion of a 3-nm NPB thin layer enhances the efficiency of charge collection by improving charge transport and reducing the interface energy barrier, resulting in better device performances. S-shaped light J–V curve appears when the thickness of the NPB layer reaches 25 nm, which is induced by the inefficient charge extraction from MEH-PPV to Ag. Capacitance–voltage measurements are performed to further investigate the influence of the NPB layer on charge collection from both simulations and experiments.